1977
DOI: 10.5636/jgg.29.29
|View full text |Cite
|
Sign up to set email alerts
|

Spectral characteristics of field variations during geomagnetically quiet conditions.

Abstract: Using data from 15 observatories at a wide distribution of latitude locations in North and South America the spectra of geomagnetic field variations having periods from 5 min to 4 hr were examined for six days of 1965 when the Ap index values were 3 or less. At high latitudes, where the maximum amplitudes occurred more poleward on low Ap days than on high Ap days, the ratio of the short to long period amplitudes was higher than at other latitudes. For all spectral samples of the data, a minimum in activity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Sq currents also changes with longitude (e.g., Campbell, 1989; Matsushita, 1967), and the geomagnetic field B modulates the ionospheric dynamo and ionospheric conductivity, thus leading to the longitudinal variations of the ionospheric dynamo currents and IHFACs (Fukushima, 1994; Olsen, 1997; Park et al., 2020; Stening, 1971; Le Sager & Huang, 2002; Takeda, 1990; Yamashita & Iyemori, 2002; Yamazaki & Maute, 2017). Matsushita and Maeda (1965) and Campbell and Schiffmacher (1985, 1986, 1988b) analyzed the characteristics of the seasonal variations for Sq currents at different longitude sectors in years of high and low solar activity, and the results showed that the vortex center parameters for internal and external Sq currents were different at different longitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Sq currents also changes with longitude (e.g., Campbell, 1989; Matsushita, 1967), and the geomagnetic field B modulates the ionospheric dynamo and ionospheric conductivity, thus leading to the longitudinal variations of the ionospheric dynamo currents and IHFACs (Fukushima, 1994; Olsen, 1997; Park et al., 2020; Stening, 1971; Le Sager & Huang, 2002; Takeda, 1990; Yamashita & Iyemori, 2002; Yamazaki & Maute, 2017). Matsushita and Maeda (1965) and Campbell and Schiffmacher (1985, 1986, 1988b) analyzed the characteristics of the seasonal variations for Sq currents at different longitude sectors in years of high and low solar activity, and the results showed that the vortex center parameters for internal and external Sq currents were different at different longitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing this 1ocational problem, Mayaud [1967] in recent years initiated the computation of new K type (and related A type) indices using an improved longitudinal distribution of mid-latitude observatories. Geomagnetic field spectra generally show an increase in amplitude with increasing period [Campbell, 1977]. This spectral characteristic causes the 3-hour range values, from which the K indices are derived, to emphasize the long-period variations in that time sample.…”
Section: Introductionmentioning
confidence: 99%
“…It is now known that the radial diffusion coefficient for energetic particles in the earth's magnetosphere is not constant as a function of time, as was often assumed in the early days of radiation belt research [Lanzerotti et al, 1970[Lanzerotti et al, , 1978. Rather, third-invariant violation depends upon the level of geomagnetic activity, as would be expected from contemporary knowledge of geomagnetic 'noise' levels [e.g., Surkan and Lanzerotti, 1974;Campbell, 1976Campbell, , 1977. As such, the radial diffusion problem is more complicated than that envisioned a decade and a half ago.…”
Section: Introductionmentioning
confidence: 99%